2015
DOI: 10.1016/j.dental.2015.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the resin cement thickness on the fatigue failure loads of CAD/CAM feldspathic crowns

Abstract: An occlusal cement thickness of 50μm was more favorable for the structural performance of feldspathic crowns than was 500μm. Cyclic fatigue reduced failure loads well below those found under monotonic loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 28 publications
3
39
0
Order By: Relevance
“…As described by Kelly et al (1996) and supported by clinical trials (Thompson et al, 1994;Hickel and Manhart, 2001), the majority of glass-ceramic crown failures initiate from flaws and tensions existing at the cementation surface, indicating this surface is the location of the highest tensile stress and/or the largest flaws. All failures found in the current study consisted of radial cracks originating from surface defects, ascribed to defects generated with acid etching for etched samples and by processing for the CTRL group, on the center of the ceramic disc at the cementation (bonding) surface of the ceramic and propagating to the periphery of the ceramic disc, in agreement with previous studies (Quinn, 2007;May et al, 2015;Venturini et al, 2017). In fragile/brittle materials such as ceramics, the onset of fractures can occur from preexisting defects on the surface or inside the ceramic material and propagate under excessive stress (usually tensile stress) (Prochnow et al, 2017) (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As described by Kelly et al (1996) and supported by clinical trials (Thompson et al, 1994;Hickel and Manhart, 2001), the majority of glass-ceramic crown failures initiate from flaws and tensions existing at the cementation surface, indicating this surface is the location of the highest tensile stress and/or the largest flaws. All failures found in the current study consisted of radial cracks originating from surface defects, ascribed to defects generated with acid etching for etched samples and by processing for the CTRL group, on the center of the ceramic disc at the cementation (bonding) surface of the ceramic and propagating to the periphery of the ceramic disc, in agreement with previous studies (Quinn, 2007;May et al, 2015;Venturini et al, 2017). In fragile/brittle materials such as ceramics, the onset of fractures can occur from preexisting defects on the surface or inside the ceramic material and propagate under excessive stress (usually tensile stress) (Prochnow et al, 2017) (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Clinically, ceramic restorations are susceptible to fatigue failure in response to an environment in the presence of moisture and cyclic masticatory forces (Gonzaga et al, 2011;Morimoto et al, 2016). Hence, fatigue failure may be defined as the cumulative damage triggered by cyclic forces, resulting in slow-crack growth of defects that will lead to catastrophic failure of a restoration under loads below the normal characteristic strength of a specific material (Wiskott et al, 1995;May et al, 2015). Although, the fatigue behavior of ZLS ceramics, including the effect of different etching protocols on the fatigue load bearing capability of the material, has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Scherrer et al 28 tested feldspathic ceramic tabs cemented to composite with resin cement thicknesses ranging from 26 ± 11 to 297 ± 48 μm and noticed a gradual decrease of the fracture strength that became statistically significant at a cement thickness of 300 μm. Gressler May et al 29 proved that under wet cyclic testing conditions, glass-ceramic crowns with an occlusal cement layer of 50 μm were more resistant than those cemented with 500 μm (246.4 ± 22.9 N vs. 158.9 ± 22.9 N). In contrast, when testing lithium disilicate tabs cemented to human dentine with a 300-μm-thick film of RelyX Ultimate, the mean fracture resistance was 1176.02 ± 159.81 N. 30 Prakki et al 31 also found that higher cement film thickness (300 μm) resulted in increased fracture resistance (982 ± 22 N) for 1-mm ceramic plates cemented to bovine dentine.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] However, this workflow is not exempt from errors, and inaccuracies that may arise during its execution [11][12][13][14] will have a cumulative effect throughout the production process, and if not controlled, threshold values [15][16][17][18][19][20][21][22][23][24][25][26][27] for the marginal and internal fit of dental restorations could be crossed, compromising the biological, esthetic, and mechanical success of such restorations. [28][29][30][31] Unfortunately, there is no consensus on what constitutes a clinically acceptable marginal and internal misfit. Threshold values reported in the literature vary from 18 to 200 μm [15][16][17][18][19][20][21][22][23][24] for the marginal fit, although a maximum clinically acceptable marginal discrepancy according to most researchers is less than 120 μm.…”
mentioning
confidence: 99%
“…Fatigue failure is considered as a fracture of the material due to progressive brittle cracking under repeated cyclic stresses at intensities below the material's normal strength [14]. Many in vitro studies have been developed involving the application of cyclic loads under moist environments to partly reproduce the clinical condition, as an attempt to infer the survival probability of ceramic restorations under different conditions [15][16][17][18][19]. In addition, Kelly et al [20] developed an in vitro test assembly that better simulates the failure mechanism and stress state observed in clinically retrieved failed prostheses (e.g.…”
Section: Introductionmentioning
confidence: 99%